2017
DOI: 10.1891/1058-1243.26.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Benefits of Childbirth Education on Future Health-Care Decision Making

Abstract: The aim of this qualitative study was to explore the perception of women regarding long-term effects of childbirth education on future health-care decision making. This qualitative study used a purposive sample of 10 women who participated in facilitated focus groups. Analysis of focus group narratives provided themes in order of prevalence: (a) self-advocacy, (b) new skills, (c) anticipatory guidance, (d) control, (e) informed consent, and (f) trust. This small exploratory study does not answer the question o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…hildbirth education is considered a predictor of patient satisfaction with care and is recommended by most obstetricians and midwives. [1][2][3] In general, providers expect childbirth education courses to cover topics important for achieving population health goals such as birth options, breastfeeding, family planning, and safe infant sleep. 2 Several population-level studies have found that childbirth education results in reduced use of cesarean delivery, one of the Healthy People 2030 objectives.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…hildbirth education is considered a predictor of patient satisfaction with care and is recommended by most obstetricians and midwives. [1][2][3] In general, providers expect childbirth education courses to cover topics important for achieving population health goals such as birth options, breastfeeding, family planning, and safe infant sleep. 2 Several population-level studies have found that childbirth education results in reduced use of cesarean delivery, one of the Healthy People 2030 objectives.…”
mentioning
confidence: 99%
“…Studies on childbirth education hypothesize that cesarean delivery can be reduced with either (1) training in comfort measures to reduce pain and the need for intervention or (2) decision counseling to reduce fear and the desire for elective cesarean delivery. Globally, there is wide variation in the number of childbirth education sessions included as part of a study whether the study investigates comfort measures or decision counseling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AEC are a significant cost to maternity services requiring careful evaluation [ 9 ]. Recently the effectiveness of AEC has come into question, with mixed findings on whether AEC have any impact on labour and birthing outcomes [ 9 , 12 , 46 , 47 ] or effect on obstetric and psycho-social outcomes [ 10 ]. Nolan and Hicks [ 11 ] have stressed that antenatal education’s survival is “dependant upon its being perceived and evaluated as a broad educational intervention and not as an obstetric one.…”
Section: Introductionmentioning
confidence: 99%
“…Many women attend childbirth preparation classes to prepare themselves for delivery, which is an important change in their lives [14]. In these classes, they are provided with information and trained to perform physical exercises and to improve their self-control capabilities, which may increase their satisfaction with the delivery experience [15,16].…”
Section: Introductionmentioning
confidence: 99%